Sophie someone - Long, Hayley, 1971- (Somerville, Massachusetts : Candlewick Press, 2017)
Sophie and her family came to live in Belgium when she was only four or five years old, but she's fourteen now and has never been quite sure why they left England in the first place. Then, one day, Sophie makes a startling discovery. Finally Sophie can unlock the mystery of who she really is.
Keywords: Identity (Psychology) -- Juvenile fiction; Families -- Juvenile fiction; Teenage girls -- Juvenile fiction; Family secrets -- Juvenile fiction; Identity -- Juvenile fiction; Family life -- Juvenile fiction; Family secrets -- Juvenile fiction; Identity (Psychology) -- Fiction; Families -- Fiction; Family secrets -- Fiction; Teenage girls -- Fiction